Peranan Unit Pelaksana Teknis Daerah Perlindungan Perempuan dan Anak Terhadap Korban Kekerasan Anak di Kota Makassar - Husnayaini Husnayaini; Muhammad Akbal; Andika Wahyudi Gani; Masni Masni (Universitas Negeri Makassar, 2022)
This study aims to determine the implementation of the Child Protection development program in dealing with victims of violence against children in Makassar City. This research uses qualitative research with a descriptive approach. Based on the source, the types of data used are primary and secondary data. Primary data were obtained through interviews with the Head of the UPT PPA, the Head of the Quick Reaction Team, the Secretary of the UPT PPA Rapid Reaction Team, Makassar City, as well as documentation and observation. While secondary data is data obtained from various literatures such as books, laws and other related sources. Processing and presentation of data is done descriptively. The results showed that the implementation of the role in dealing with women victims of violence UPTD PPA Makassar City, providing health recovery assistance to children victims of violence, providing psychological assistance to children victims of violence, providing legal assistance to children victims of violence, the role of providing psychoeducation in the environment around the victims, the role of providing social rehabilitation to victims of violence.